EFL Material To Improve Oral Skills Through The Use Of Idiomatic Expressions In Preteens Learners (2021)
The objective of this degree project is the design, implementation and evaluation of digital teaching material; this focuses on learning English, specifically, speaking skills. The development of this material is based on some theories, techniques and didactic and technological tools, such as task-based learning (TBL), the lexical approach, idiomatic expressions, the use of digital tools (Google Classroom) and feedback. Taking these aspects into account, a diagnostic test and an evaluation rubric designed by the teacher were carried out, which made it possible to identify the difficulties of students of around 11 years old in the English course developed by the Antonio Nariño University. Later, the creation of a didactic material was proposed for the students to improve their oral skills in the language; this was implemented for two months, which helped them overcome the aforementioned difficulties. It is important to state that the material was evaluated by external experts, who made some recommendations that were taken into account for its improvement.